Mild brain injury and anticoagulants: Less is enough. Issue 4 (August 2017) - Campiglio, Laura; Bianchi, Francesca; Cattalini, Claudio; Belvedere, Daniela; Rosci, Chiara Emilia; Casellato, Chiara Livia; Secchi, Manuela; Saetti, Maria Cristina; Baratelli, Elena; Innocenti, Alessandro; Cova, Ilaria; Gambini, Chiara; et al.
Abstract: Background: Despite the higher theoretical risk of traumatic intracranial hemorrhage (ICH) in anticoagulated patients with mild head injury, the value of sequential head CT scans to identify bleeding remains controversial. This study evaluated the utility of 2 sequential CT scans at a 48-hour interval (CT1 and CT2) in patients with mild head trauma (Glasgow Coma Scale 13–15) taking oral anticoagulants. Methods: We retrospectively evaluated the clinical records of all patients on chronic anticoagulation treatment admitted to the emergency department for mild head injury. Results: A total of 344 patients were included, and 337 (97.9%) had a negative CT1. CT2 was performed on 284 of the 337 patients with a negative CT1 and was positive in 4 patients (1.4%), but none of the patients developed concomitant neurologic worsening or required neurosurgery. Conclusions: Systematic routine use of a second CT scan in mild head trauma in patients taking anticoagulants is expensive and clinically unnecessary.